Gold work, filing and blackened teeth dental modifications in Luzon - Zumbroich, Thomas J.; Salvador-Amores, Analyn Ikin V. (2010)
Different forms of dental modifications used to be a widespread cultural expression across much of Luzon (Philippines). Gold decorations on teeth appear in the archaeological record around the fourteenth century CE, and later Spanish documents confirm gold pegging, but also teeth filing as well as the deliberate blackening of dentitions among Tagalog and Bikol speakers. While in the immediate sphere of Spanish influence such practices were rapidly abandoned, they persisted far longer among indigenous groups in more remote locales, especially the Cordillera. The motivations behind dental modifications were complex and included concepts of beautification, achieving personhood and affirming group identity. By the beginning of the twenty-first century the practices had generally fallen into disuse, though to this date an appreciation of and familiarity with the techniques of teeth blackening is being preserved among an ever shrinking number of elders of certain indigenous groups, such as the Gaddang.
Keywords: Teeth -- blackening; Teeth -- Mutilation -- Philippines; Dental anthropology